1995
DOI: 10.1111/j.1365-2230.1995.tb01351.x
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and risks of intralesional corticosteroid injection in the treatment of dermatological diseases

Abstract: Intralesional corticosteroid (CS) injections have been used to treat a variety of dermatological and non-dermatological diseases with variable results. The purpose of the injection is to attain a high concentration of the drug at the diseased site, with minimal systemic absorption. Several CS preparations are available for intralesional injection, although triamcinolone derivatives have gained the widest usage in dermatology. The dose and the interval between injections depend on the type, size and severity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
78
0
17

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(95 citation statements)
references
References 60 publications
0
78
0
17
Order By: Relevance
“…These effects then produce local tissue atrophy, or, in extreme cases, necrosis 2 . Although the exact pathogenesis of hypopigmentation is unknown, the corticosteroid may reduce the number or activity of melanocytes 1 . Corticosteroids might also alter melanocyte function by inhibiting prostaglandin or cytokine production in various epidermal cells, and may suppress secretory metabolic products from melanocytes without causing their destruction 6 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These effects then produce local tissue atrophy, or, in extreme cases, necrosis 2 . Although the exact pathogenesis of hypopigmentation is unknown, the corticosteroid may reduce the number or activity of melanocytes 1 . Corticosteroids might also alter melanocyte function by inhibiting prostaglandin or cytokine production in various epidermal cells, and may suppress secretory metabolic products from melanocytes without causing their destruction 6 .…”
Section: Discussionmentioning
confidence: 99%
“…The exact pathogenesis of linear hypopigmentation or atrophy is also unknown. The most widely accepted mechanism is the lymphatic spread of the corticosteroid suspension and resulting linear hypopigmentation or atrophy of skin tissues 1 . After injecting Evans Blue Dye or Alphazurine 2 G (Patent Blue) into atrophic lesions, Kikuchi and Horikawa 7 concluded that the lesions were related to lymphatic vessels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Atrophy and pigment changes can regress in weeks or they may become permanent for a long time or even completely. Even systemic side effects may very rarely occur, such as Cushing's syndrome, allergic reactions, adrenal suppression, syncope, ptosis, blindness, and hyperglycemia (9).…”
Section: Discussionmentioning
confidence: 99%
“…The most common side effects are local side effects, such as atrophy, hypopigmentation, pain, bleeding, telangiectasia, hypertrichosis, folliculitis, delay in wound healing, ulcers, secondary infections, perilesional linear atrophy and hypopigmentation, allergic reactions, calcifications, and granuloma formation (8,9). Atrophy and pigment changes can regress in weeks or they may become permanent for a long time or even completely.…”
Section: Discussionmentioning
confidence: 99%